Balanced scorecard as a organizational performance measurement tool and an application - Damgacı, Veyis (My University, 2009)
Increasing competitiveness, changing and dynamic business environment and globalization force the firms to change and strategic management. Characteristic of strategic management are ability of firms to create competitive advantages in long term and can be not be transferable. This new environment forces the organizations to control and monitor their organizational performance, evaluate their strategies and making revision is needed. Therefore Balanced Scorecard is an efficient tool for evaluating organizational performance and making foresights about future. This study reviews the Balanced Scorecard which is a strategic performance management tool. In first and second part general information about balanced scorecard is given. In third and forth part, it’s considered what has to be done before implementation and the steps that were followed in implementation phase are explained. In fifth part Balanced Scorecard that was explained theoretically tried to be implemented.

Artan rekabet, hızla değişen dinamik iş ortamı ve globalleşme işletmeleri değişime ve stratejik yönetime zorlamaktadır. Stratejik yönetimin özelliği firmaya uzun vadede rekabet avantajı sağlaması ve transfer edilemeyen bir bilgi olmasıdır. Bu yeni ortam organizasyonların kurumsal performanslarını kontrol etmelerini, gözetlemelerini, stratejilerini değerlendirmelerini ve yeniden planlamalarını zorunlu hale getirmiştir. Burada kurumsal performans karnesi (Balanced Scorecard) hem mevcut performansı değerlendirmek hem de geleceğe yönelik ön görüler oluşturmak için oldukça etkili bir araçtır. Bu çalışmada, stratejik performans yönetiminde kullanılan yöntemlerden biri olan kurumsal performans karnesi incelenmiştir. Öncelikle kurumsal performans karnesi hakkında genel bilgi verilmiştir. İkinci bölümde uygulama öncesi yapılması gerekenler irdelenmiş, uygulama geliştirme sürecinde takip edilecek adımlar açıklanmış, kullanılacak yöntemler irdelenmiştir. Son bölümde ise teorik olarak incelenen kurumsal performans karnesinin bir işletmede uygulaması gerçekleştirilmeye çalışılmıştır.
Keywords: Stratejik Yönetim